Easy preparation of gold nanostructures supported on a thiolated silica-gel for catalysis and latent fingerprint detection. (August 2018) - Andrade, George R.S.; Nascimento, Cristiane C.; Santos, Yane H.; Costa, Luiz P.; Almeida, Luís E.; Gimenez, Iara F.
Abstract: Herein, we report an extremely simple, fast and controllable method for preparing gold nanoclusters (GNC) and gold nanospheres (GNS) in situ onto a thiol-organofunctionalized silica gel (MPS) for catalysis and detection of latent fingerprints (LFPs). The silica gel surface was suitably modified with thiol groups by a silylation reaction method using 3-(mercaptopropyl)trimethoxysilane (MPTS). Spectroscopic data (UV-visible-NIR and PL) have shown that the as-prepared thiol-modified silica is able to reduce Au 3+ ions in situ, producing orange-red light emitting GNCs. For preparing GNS, on the other hand, it was necessary an adsorption step followed by a reduction with NaBH4 . Various experimental conditions for the preparation of GNS were studied, such as the gold precursor and reducing agent concentrations and the reaction time. TEM, XRD and UV-visible-NIR analyses showed, respectively, the presence of approximately spherical particles with a face-centered cubic structure and a plasmon resonance band, which is controllable by changing those synthesis parameters. The as-prepared samples have shown high catalytic activity for the reduction of an AZO dye in aqueous solution, being able to decolorize 92% of the dye content within only 40 min. GNS/MPS and bare MPS have also shown enhanced activity for detecting LFPs deposited over porous and non-porous surfaces, including glass, polymer, paper, metal, leather, ceramic and wood. Our method has shown to be a suitable alternative for conventional techniques, it is easier to apply, fast-responsive, reusable, durable and thermally stable. Graphical abstract: Highlights: A simple method for preparing Au nanostructures onto a thiolated silica was reported. Morphological and optical properties vary with the precursor amount and reaction time. The as-prepared material showed enhanced catalytic activity toward AZO dye reduction. The nanocomposite was used as safe, simple treatment to visualize latent fingerprints. Allows detection of latent fingerprints on various porous and non-porous surfaces.